Correlation of blood-based immune molecules with cardiac gene expression profiles reveals insights into Chagas cardiomyopathy pathogenesis - Souza-Silva, Thaiany G.; Neves, Eula G. A.; Koh, Carolina; Teixeira-Carvalho, Andrea; Araújo, Silvana Silva; Nunes, Maria do Carmo Pereira; Gomes, Juliana de Assis Silva; Gollob, Kenneth J.; Dutra, Walderez Ornelas (Frontiers in Immunology, 2024)
Understanding compartmentalized immune responses in target organs is crucial for elucidating the pathogenesis of various diseases. However, obtaining samples from affected vital organs often poses safety challenges. In this study, we aimed to investigate potential correlations between the levels of disease-associated immune molecules in the bloodstream with their gene expression profiles in the hearts of patients suffering from Chagas Cardiomyopathy (CCC). This debilitating and often fatal condition is caused by infection with the protozoan Trypanosoma cruzi. Blood samples were analyzed using the Bio-Plex platform. Gene Expression Omnibus (GEO) database was used to determine gene expression profile in heart tissue from CCC and non-Chagas controls (CTRL). Elevated levels of inflammatory cytokines were detected in the plasma of CCC patients, and these levels correlated with clinical indicators of deteriorating cardiac function. Notably, 75% of the soluble factors assessed in the plasma exhibited a consistent relationship with their gene expression levels in the cardiac tissue of CCC patients. Analysis of interactions and signaling pathways related to these molecules revealed an overrepresentation of inflammatory pathways in both blood and heart compartments. Moreover, we identified that differentially expressed genes in CCC cardiac tissue were primarily associated with Tcell signaling pathways and correlated with the presence of CD8+ T cells in the myocardium. Our findings establish a strong correlation between relevant immune molecules and their signaling pathways in both the blood and heart tissue in CCC. This validates the use of blood as a non-invasive medium for understanding immunopathology and identifying markers for cardiac dysfunction in Chagas disease.